Penafsiran Warna-Warna Tradisional Bali dalam Buku Autobiografi Seniman I Made Ada dan Made Wianta Melalui Pendekatan Hermeneutika - Asthararianty, Asthararianty (Institute of Research and Community Outreach - Petra Christian University, 2013)
The use of color that occurs in some cultures is seen in Balinese, Javanese, and Minangkabau cultures, as well as a few places around the island. These colors state their respective regions, making them the region’s traditional color. These colors must intersect with the culture of origin of each area. In the process, each region and its culture each has a set of media in demonstrating their color richness. Be it in the form of traditional arts, such as puppet, or dance with the beauty of the clothes, they give the hallmark of their respective regions. Likewise, art from Bali which appears identical to the results of their work is beautiful, interesting and very attractive. Based on this development, then how is the position of the traditional colors in this modern era, especially in Bali? How is the position of the traditional colors in the eyes of some Balinese artists to books which the contents are about themselves? This problem is seen through an interpretation by referring to existing theories of the books that perpetuate each artist’s work and themselves at work.